Implementation of ESBN (Educational Serial Book Number) in Improving Access and Quality of Education - Yudha, S.Pd, M.Ed TESOL, Rahmat Putra (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2023)
Methods are the key to achieving progress and sustainable development in a society. However, the challenge of accessing quality education remains a global problem, especially in less developed regions. In an attempt to address this problem, the concept of ESBN (Educational Serial Book Number) has emerged as a potential solution. ESBN is a serial numbering system applied to educational materials, allowing education managers to more effectively record, track, and monitor educational resources. This paper presents an overview of the concept, implementation, impact, and benefits of using ESBNs in improving accessibility and quality of education. Through the analysis of ESBN concepts, we explain how ESBN can improve the accessibility of education by facilitating a more equitable distribution of educational materials and easier online access. We are also exploring the impact of using ESBNs on the quality of educational materials through more effective monitoring and evaluation. By implementing the ESBN concept effectively, it is expected to create a more inclusive, measurable, and quality educational environment for all individuals, thus encouraging the achievement of sustainable development goals in the field of education.